Kartu Sadari Bullying: Media Pembelajaran dalam Mengembangkan Keadaban Kewarganegaraan - Hambali; Hariyanti; Permady, Gigieh Cahya; Istianah, Anif; Abdillah, Fauzi (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
Descriptive qualitative design is used in this study to describe the understanding of students and teachers in schools about bullying, as well as the construction of bullying prevention ideas through bullying awareness card learning media. The location of the study was in Dumai, by interviewing several students and teachers in schools. The results of the study showed that (1) students and teachers have diverse understandings and perspectives on bullying; (2) the absence of learning media that supports the campaign and socialization of bullying behavior in schools so far. Preventive steps can be taken through bullying awareness card learning media which is a card game media that contains material on the concept, how to prevent and handle bullying in schools. This study recommends that schools use bullying awareness card learning media in integrated subjects with character education such as citizenship education, guidance and counseling and religious education. This is intended to develop students' civic virtue so that they become tolerant and compassionate citizens in diversity.